Effects of Boko Haram and Environmental Hazard on the People of Borno and Adamawa State, Nigeria - Buba Kefas (International Journal of Climate Conditions, 2025)
This study focuses on the effects of environmental hazards and Boko harams on the people of Borno and Adamawa State. Environmental hazards and Boko haram disasters especially, those that occur as a result of natural phenomena as one of the greatest threats to humanity and economic development. Causes and the effect of Boko Haram and the Environmental hazard were studied. Man-made disasters such as conflicts, crisis and wars also use to take human lives in some instance. While examining this, researchers use to forget millions that are not killed during such events, but who suffered deadly risks of environmental hazards. This study focused on the mode of survival of the people who are left behind after the occurrence of man-made disaster. Primary data were obtained from the people of the states by selecting local government areas from each state and administering questionnaires. The study involved a sample size of 200 respondents and 8 Focus Group Discussions (FGDs): the local government areas were Guyuk, Michika, Monguno, and Kukawa. The result also reveals that The Boko Haram members are mostly youth of either school age or economically active group who were not able to go to school because of the economic situation of the country or unemployed parents. The study further recommended the need to establish more schools for children who left their schools after displacement. A proper sewage disposal system should be made in the town artery houses should have toilets and public toilets should be provided in marketplaces and other places where people lives.
Keywords: Environment; hazard; man-made disasters; public health infrastructure; survival strategies